Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/ps.888
|View full text |Cite
|
Sign up to set email alerts
|

Bound and unextractable pesticidal plant residues: chemical characterization and consumer exposure

Abstract: Plants are well known to incorporate pesticides into bound and unextractable residues that resist solubilization in common laboratory solvents and are therefore not accessible to standard residue analysis. A characterization of such residues has been proposed for incorporation rates above trigger values of 0.05 mg kg(-1) parent pesticide equivalents, or percentage values of 10% (United States Environmental Protection Agency, 1995) or 25% (Commission of the European Communities, 1997) of the total radioactive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 73 publications
(93 reference statements)
1
23
0
Order By: Relevance
“…Although lower amounts of applied radioactivity were taken up by C. dactylon, absorbed propanil equivalents were similar as in the other two plants due to the higher concentration and the smaller biomass of the plant. All propanil equivalents in the experiments exceeded previous proposed trigger values (0.1-0.5 mg/kg, dry commodities) of the herbicides, similar to the findings summarized by Sandermann (2004).…”
Section: Extractable Fractions and Non-extractable Fractions (Ner)supporting
confidence: 82%
“…Although lower amounts of applied radioactivity were taken up by C. dactylon, absorbed propanil equivalents were similar as in the other two plants due to the higher concentration and the smaller biomass of the plant. All propanil equivalents in the experiments exceeded previous proposed trigger values (0.1-0.5 mg/kg, dry commodities) of the herbicides, similar to the findings summarized by Sandermann (2004).…”
Section: Extractable Fractions and Non-extractable Fractions (Ner)supporting
confidence: 82%
“…In other work, an altered distribution of bound metabolites between pectins and hemicelluloses in suspended cells compared with plant stems was explained by the lack of secondary wall development in cultured plant cells (Laurent and Scalla, 1999). There is evidence that bound residues accumulate with time in plants as the amounts of free and soluble metabolites decrease (Sandermann, 2004); this suggests that measurements of bound components in plant tissue cultures may underestimate the levels characteristic of whole plants. Yet, in other studies, cultured plant cells have been found to generate levels of bound residues similar to those found in whole plants Schmidt et al, 1993).…”
Section: Localization Studiesmentioning
confidence: 97%
“…The nonextractable or bound residues of plant cells have attracted considerable interest in recent years because of concerns that the persistence of chemical residues in edible plants may allow toxic components to enter the food chain (Sandermann, 2004). Nonextractable residues are associated primarily with cell walls: incorporation of metabolites in covalent and noncovalent linkage with proteins, lignin, pectin, polysaccharides, cellulose, hemicellulose, starch, and cutin has been reported (Sapp et al, 2003).…”
Section: Localization Studiesmentioning
confidence: 99%
See 2 more Smart Citations